2019
DOI: 10.1002/jat.3795
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the N‐methyl‐d‐aspartate receptor is involved in glyphosate‐induced renal proximal tubule cell apoptosis

Abstract: Glyphosate-based herbicides have been used worldwide for decades and have been suggested to induce nephrotoxicity, but the underlying mechanism is not yet clear.In this study, we treated a human renal proximal tubule cell line (HK-2) with glyphosate for 24 hours at concentrations of 0, 20, 40 and 60 μM. Glyphosate was found to reduce cell viability and induce apoptosis and oxidative stress in a dose-dependent manner. Because the chemical structures of glyphosate and those of its metabolite AMPA are similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…Leung et al [ 103 ], using MDCK cells and proximal tubule-like opossum kidney cells, additionally showed that immoderate activation of the NMDAR (10 mM glutamate), as well as the excessive blockade of this receptor with MK-801 or CPP led to harmful effects on survival of kidney cells [ 103 ]. Recent work from Gao et al [ 104 ] showed that NMDAR activation caused by glyphosate treatment led to increased oxidative stress and apoptotic death of renal epithelial cells, while blockade of NMDAR ameliorated glyphosate-induced cell damage [ 104 ].…”
Section: Distinctive Physiological and Pathophysiological Roles Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Leung et al [ 103 ], using MDCK cells and proximal tubule-like opossum kidney cells, additionally showed that immoderate activation of the NMDAR (10 mM glutamate), as well as the excessive blockade of this receptor with MK-801 or CPP led to harmful effects on survival of kidney cells [ 103 ]. Recent work from Gao et al [ 104 ] showed that NMDAR activation caused by glyphosate treatment led to increased oxidative stress and apoptotic death of renal epithelial cells, while blockade of NMDAR ameliorated glyphosate-induced cell damage [ 104 ].…”
Section: Distinctive Physiological and Pathophysiological Roles Ofmentioning
confidence: 99%
“…Inhibition of NMDAR by MK-801 significantly reduced glomerular Nox activity, Nox-dependent O 2 production and lipid peroxidation induced by hyperhomocysteinemia (hHcys) in rat kidneys, suggesting an important role of the NMDAR in activation of Nox system in the kidney during hHcys and in the development of hHcys-induced glomerulosclerosis [ 59 ]. Furthermore, blockade of NMDAR attenuated glyphosate-induced increase of Ca 2+ influx and reduced activity of major endogenous antioxidant enzymes such as SOD, CAT and GSH-Px in HK-2 cells, strongly suggesting that activation of NMDAR, accompanied by Ca 2+ influx and oxidative stress, is involved in glyphosate-induced renal proximal tubule epithelium apoptosis [ 104 ]. Treatment of Sprague-Dawley rats with gentamicin led to an increase of endothelin type B receptor (ETBR) in the renal cortex and urinary nitrite concentration, while MK-801 managed to normalize the levels of urinary nitrites [ 102 ].…”
Section: Nmdar-mediated Signaling Pathways In the Kidneymentioning
confidence: 99%
“…Gao et al (2019) [150] use a cell culture model to show that the kidney is damaged by glyphosate-based herbicides and that the renal proximal tubule may be a main target. Though the toxicity of commercial formulations is well established, the authors demonstrate that glyphosate, the active ingredient of glyphosate-based herbicides, injures renal tubule epithelial cells via the NMDAR1/calcium influx/oxidative stress pathway, both in vitro and in vivo.…”
Section: Synergy Between Glyphosate and Other Toxic Elementsmentioning
confidence: 99%
“…Previous evidence have implicated these eicosanoids in a host of inflammatory disorders, and thus cPLA 2 may play an important role in the development of inflammatory diseases (19)(20)(21). Furthermore, our previous study (11) demonstrated that oral exposure of glyphosate at a dose of 400 mg/kg in mice resulted in intracellular calcium ([Ca 2+ ] i ) overload and overproduction of reactive oxygen species (ROS). This suggested that cPLA 2 may be involved in renal tubular damage induced by glyphosate.…”
Section: Introductionmentioning
confidence: 97%
“…Our previous studies demonstrated that glyphosateinduced nephrotoxicity was dependent on the activation of N-methyl-D-aspartate receptors (NMDARs) expressed in the proximal tubular epithelium. This resulted in the elevation of cytoplasmic calcium ions (Ca 2+ ) and oxidative damage (11).…”
Section: Introductionmentioning
confidence: 99%